GROWING STUDENT INTEREST IN READING AND READINESS IN LEARNING THROUGH HABIT ACTIVITIES IN CLASS X IPS SMA NEGERI 3 RANGKASBITUNG - Windradi, Asep Yadi (Journal Learning Geography, 2023)
The main problem found in the students of SMA Negeri 3 Rangkasbitung is the low interest and reading behavior that affects students' readiness to participate in the learning process. In general, the problem-solving strategy used is to direct students to certain behaviors, namely fond of reading through habituation activities. The development of interest and good reading habits should begin as early as possible in childhood. Parents, especially mothers, and teachers, especially Playgroup, Kindergarten, and Elementary School teachers, have a very decisive role in these development efforts. The development of interest and reading habits should start at home. Meanwhile, schools are obliged to foster reading interests and habits that have been developed at home. Support the compulsory reading program at a certain time outside school activities, because reading is a very basic activity in a series of learning activities. Interest and good reading habits are impossible to have in a short time. Its development takes a relatively long time, and must be in line with educational developments that occur in society. The habituation process is expected to have a positive impact on students during the learning process. The learning process can run optimally, if students have readiness to learn, one of which is that students first have reference material through reading activities. The literacy movement is more developed towards subjects, meaning that books read by students are according to the subjects studied by students. Each subject requires students to finish reading several reference books within a certain period of time.